A Town Called Asbestos: Environmental Contamination, Health, and Resilience in a Resource Community - Mellor, Robynne (Labour / Le Travail, 2017)
The article reviews the book, "A Town Called Asbestos: Environmental Contamination, Health, and Resilience in a Resource Community ,"by Jessica Van Horssen.